Patient-derived solitary fibrous tumour xenografts predict high sensitivity to doxorubicin/dacarbazine combination confirmed in the clinic and highlight the potential effectiveness of trabectedin or eribulin against this tumour. (May 2017) - Stacchiotti, S.; Saponara, M.; Frapolli, R.; Tortoreto, M.; Cominetti, D.; Provenzano, S.; Negri, T.; Dagrada, G.P.; Gronchi, A.; Colombo, C.; Vincenzi, B.; Badalamenti, G.; et al.
Abstract: Background: Preclinical models that mimic pathological and molecular features of solitary fibrous tumour (SFT) represent an important tool to select effective regimes and novel compounds to be tested in the clinic. This study was aimed at developing two preclinical models of SFT, assessing their predictive value in the clinic and selecting potential novel effective treatments. Material and methods: Two dedifferentiated-SFT (D-SFT) models obtained from patients' biopsies were grown in immunodeficient mice. The antitumour activity on these models of doxorubicin, dacarbazine (DTIC), ifosfamide (monotherapy or combination), trabectedin and eribulin was tested. Twelve SFT patients were treated with doxorubicin and DTIC. Response by RECIST, progression-free survival and overall survival were retrospectively evaluated, distinguishing malignant-SFT (M-SFT) and D-SFT. Results: Two D-SFT patient-derived xenografts (PDXs) that represent the first available preclinical in vivo models of SFT were developed and characterised. Doxorubicin/DTIC, DTIC/ifosfamide, doxorubicin/ifosfamide combinations consistently induced better antitumour activity than the single-agents. Particularly, doxorubicin/DTIC combination caused a max tumour volume inhibition >80% in both models. Doxorubicin/DTIC combo showed activity also in the case-series. Best RECIST responses were: 6 responses (M-SFT = 2 of 7, D-SFT = 4 of 5), 1 stable disease, 5 progressions, with a 6-month median progression-free survival (M-SFT = 6, D-SFT = 10 months). The PDXs were very sensitive to trabectedin and eribulin. Conclusion: Doxorubicin plus DTIC combination was effective in our two D-SFT mice models and appeared to be active also in the clinic, especially in high-grade D-SFT patients. Among additional drugs tested in the PDXs, trabectedin and eribulin were highly effective, providing a rational to test these drugs in D-SFT patients. Highlights: Doxorubicin plus DTIC showed a high antitumour effect against 2 PDX models of dedifferentiated-solitary fibrous tumour (SFT). Their activity was confirmed in a small retrospective series of advanced SFT patients (50% of partial responses by RECIST). Even trabectedin and eribulin showed a great antitumour effect in the PDX models. Based on these results, a phase 2 trial on doxorubicin/DTIC versus trabectedin is starting. Eribulin, recently approved for treatment of liposarcoma, deserves further investigation in SFT.